A non-invasive technique for sex determination of monomorphic birds - Jessey Angat,; Farida Zuraina Md Yusof, (Malaysian Society of Applied Biology, 2015)
We report on the unambiguous identification of monomorphic bird from a freshly plucked feather in Gunung Ledang, Taman Negara, Johor. Genetic analysis accurately recognizes gender by comparing the intron length between CHDZ and CHDW that is preserved within the avian Z and W sex chromosomes. The species under study were Stripe-throated Bulbul (Pycnonotus finlaysoni), Olive-winged Bulbul (Pycnonotus plumosus), White-throated Kingfisher (Halcyon smyrnensis) and Collared Scops Owl (Otus lettia). PCR amplification using P2/P8 primer pairs produced single band in male (ZZ) and two bands in female (ZW) birds that ranged between 300-400 base pairs in length. The PCR products were confirmed by the preliminary experiment of known sex of both species of polymorphic birds. Thus, this PCR-based test is fast, accurate and applicable in these species. Therefore, it could be used for many conservation studies notably in threatened or rare species.